The Course of Generalized Meningococcal Infection Caused by Meningococcus Serogroup W135 - M. V. Ivanova; N. V. Skripchenko; A. A. Vilnits; E. Yu. Gorelik; N. V. Matyunina; K. V. Serednyakov (LLC "Diagnostics and Vaccines", 2016)
The article describes the features of the course of generalized meningococcal infection caused by W135 serogroup meningococcus in children of various age groups. Taking into account the load of the disease course, especially in children of older age, vaccination by tetravalent (A, C, W, Y) conjugated vaccine is recommended not only for children of early age but also adolescents.